Multi Factor Entrepreneurial Spirit of Food Entrepreneurs: Before and After The Covid-19 Pandemic - Tuti, Meylani; Syarif, Rizal (Indonesian Journal of Business and Entrepreneurship, 2022)
Entrepreneurship has become a sector considered by the government in creating jobs for the community. Entrepreneurs are the focus of the entrepreneurial process that must receive special attention in increasing interest in entrepreneurship among the younger generation. Efforts to develop entrepreneurship have been carried out by the government and private agencies through coaching programs, especially for novice entrepreneurs who are just starting their business as food entrepreneurs. In this research, the authors would like to examine if there are differences in the variables of self-efficacy, motivation, competence, and creativity with factors that differentiate based on age, geographic area, gender, parental background as entrepreneurs, having other jobs, having businesses after and before the COVID-19 pandemic. and opinions about the impact of the COVID-19 pandemic on them. By using Mann Whitney that is used to decide the difference in the median of the 2 independent groups. The results displayed that based on of age, geographical area, having another job, having a business after and before the COVID-19 pandemic, and the impact of the pandemic there was no difference in self-efficacy, motivation, competence, and creativity. Differences happen in the variables of motivation, competence and creativity based on gender. In the competence and creativity variables, there are differences based on parents who have entrepreneurial backgrounds. The managerial contribution in this research is that universities must take different approaches to male and female students and students who have family backgrounds as entrepreneurs.Keywords: self-efficacy, competence, motivation, creativity, food entrepreneur, gender, age